Strategi Koping dan Skor DASS pada Perawat yang Bertugas di Ruang Isolasi COVID-19: Sebuah studi cross-sectional - Adinoto, Septo Pero; Fitrikasari, Alifiati; Wardani, Natalia Dewi; Noerhidajati, Elly (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUNDS: Nurses are at risk for mental health problems while caring for Corona Virus Disease 2019 (COVID-19) patients. The COVID-19 pandemic had impacted not only on emotions but also nurses' coping strategies. The difference between this study and previous research in this study adds up the total DASS 42 (Depression Anxiety Stress Scale) scores as parameter to assess mental health problems of the subjects. OBJECTIVE: To determine the association between coping strategies and the DASS score among nurses on duty in the COVID-19 isolation room of Dr Kariadi Hospital. METHODS: This cross-sectional study involved nurses who treated patients in the COVID-19 isolation ward, the COVID-19 intensive room, and the COVID-19 emergency room. All participants were involved by the consecutive sampling method. The research instrument used a sociodemographic questionnaire, the Brief COPE, and the DASS 42. Inclusion criteria included nurses who served in the COVID-19 isolation room and aged 22-60 years. Higher DASS score indicates that the subject is experiencing general psychological distress compared to subjects with a lower score. RESULTS: Most of the respondents in this study (n=112 subjects) had problem-focused coping strategies. The mean DASS score on the subjects is 14.29 ± 13.25. There was an association between coping strategies (p=0.048), sex (p < 0.001), place of work (p = 0.041), and DASS score. CONCLUSION: There was a relationship between coping strategies and the DASS score of nurses on duty in the COVID-19-19 isolation room. Further research needs to explore environmental factors and social support, also examine physical illnesses in more detail.